ChemInform Abstract: Gold‐Catalyzed Cyclization and Cycloisomerization of Yne‐Tethered Ynamide: The Significance of a Masked Enol‐Equivalent of an Amide. Issue 10 (February 2016) - Nayak, Sanatan; Prabagar, B.; Sahoo, Akhila K.
Abstract: Review: [12 refs.